Separation of Mycobacterium smegmatis From a Mixed Culture Using the Cell Wall Binding Domain of D29 Mycobacteriophage Endolysin - Nair, Gokul; Jain, Vikas (Frontiers in Microbiology, 2020)
Pathological infection caused by Mycobacterium tuberculosis is still a major global health concern. Traditional diagnostic methods are time-consuming, less sensitive, and lack high specificity. Due to an increase in the pathogenic graph of mycobacterial infections especially in developing countries, there is an urgent requirement for a rapid, low cost, and highly sensitive diagnostic method. D29 mycobacteriophage, which is capable of infecting and killing Mycobacterium tuberculosis, projects itself as a potential candidate for the development of novel diagnostic methods and phage therapy of mycobacterial infections. In our previous study we showed that the cell wall-binding domain (CTD) located at the C-terminal end of the D29 mycobacteriophage LysA endolysin very selectively binds to the peptidoglycan (PG) of M. smegmatis and M. tuberculosis. Here, by using M. smegmatis as model organism and by exploiting the PG binding ability of CTD, we have developed a method to isolate M. smegmatis cells from a mixed culture via magnetic separation. We show that green fluorescent protein (GFP)-tagged CTD (CTD-GFP) can bind to M. smegmatis cells in vitro after treatment with nonionic detergent Triton X-100. Fluorescence-based assays show that CTD-GFP binding to M. smegmatis cells is highly specific and stable, and is not disrupted by an excess of either GFP or BSA. We further fused CTD with Glutathione-S-Transferase (GST) to generate CTD-GST protein and carried out an anti-GST antibody-mediated coating of CTD-GST on Dynabeads. This allowed us to perform successful magnetic separation of M. smegmatis from a mixed culture of bacteria having both Gram-negative and Gram-positive bacteria. Furthermore, the separated cells could be confirmed by a simple PCR. Thus our assay allows us to separate and identify M. smegmatis from a mixed culture.